THE IMPLEMENTATION OF SERIES PICTURE TOWARDS STUDENTS’ SPEAKING ABILITY AT THE SECOND SEMESTER OF THE TENTH CLASS AT MA. AL-HIKMAH BANDAR LAMPUNG IN 2010/2011 - Syafrizal .; Bambang Suwarno (Universitas Bengkulu, 2016)
A series picture is a sequence of picture dealing with one subject. It may tell a story, present an event, describe a scene, reveal a person, or show how to do something. From the previous studies, series picture has been demonstrated as practical teaching and learning media for students at all grade levels. This method has been identified by researchers as an excellent media for increasing vocabulary and improving writing competence. However, the use of series picture as media for speaking has been relatively unexplored. The objective of this study is to investigate the influence of series picture as media to improve students’ speaking ability. The research design of this study was pre- experimental design. The population was the tenth grade students of MA Al-Hikmah Way Halim Bandar Lampung in the academic year of 2010/2011 and samples consisted of 32 students. The data was collected via test, observation and interview. In analyzing thedata, t test formula was used, it was found that t ratio is 3.45 and ttable for a = 0.01 the ttableis 2.46 and for a = 0.05 the ttable is 1.70 it meant that t ratio was higher than t table. Thefinding showed positive feedback received from the subject on the use series picture fortheir speaking ability. Based on the result of this study, it can be concluded that series picture as media is very effective to improve students’ speaking ability.